Vive la Différence? Comparing “Like with Like” in Studies of Learners’ Ideas in Diverse Educational Contexts - Keith S. Taber (Education Research International, 2012)
This paper considers the status of educational research that looks to replicate previous findings in a novel educational context, taking as its focus an active area of research in a range of national contexts: studies into students’ ideas about scientific topics. The paper considers the circumstances under which a “replication” study should be considered to offer original new knowledge worthy of publication in international research journals. It is argued here that there are sound principled reasons to expect studies undertaken in different educational contexts to be able to contribute to a progressive research programme, and so researchers should be encouraged to undertake such work. However, technically competent papers submitted to prestigious journals will be rejected if they are considered to merely replicate previous work without offering novel empirical or theoretical content that is considered to make an original contribution. This paper explores the basis for welcoming research “testing-out” published findings in new contexts and considers the place of such studies within a progressive research programme. This analysis can inform research design for those looking to explore learners’ ideas in local educational contexts, by offering clear guidance on the forms of research likely to offer significant contributions to public knowledge.